A contrastive between English and Batak Toba language in kinds of adverb - Siahaan, Carolina; Ito Hutahaean, Rossa; Yani Gea, Ephy Cryday; Teresia Lubis, Hotnida; Sinaga, Miranda; Panjaitan, Anita; Herman, Herman (Journal of Education, Linguistics, Literature, and Art, 2024)
The research aims to identify potential challenges Indonesian students may encounter while learning English as a foreign language. This research identify the differences and similarities between adverbs in English language (EL) and Toba Language (TL) using a contrastive analysis methodology. Adverbs are essential elements of grammar, influencing the structure of expressions in both languages. The study employs qualitative descriptive research, generating written descriptions of the objects under investigation. By comparing the adverbs in EL and TL. The analysis covers forms, meanings, and positions of adverbs in both languages. The findings may provide valuable insights and recommendations for both English-speaking teachers and Indonesian educators to enhance the teaching and learning process of English to Indonesian students. The research contributes to the understanding of the linguistic differences between English and TL, aiding language learners in mastering these languages more effectively.